SIMTOMATOLOGI DAN WAKTU KEMATIAN RAYAP Macrotermes gilvus Hagen (ISOPTERA: FAMILI TERMITIDAE) SETELAHINFEKSI CENDAWAN Metarhizium brunneum Petch - Muhammad Sayuthi; Teguh Santoso; Idham Sakti Harahap; Utomo Kastosuwondo (Research Center for Biology-Indonesian Institute of Sciences, 2011)
The potential of entomopathogenic fungus Metarhizium brunneum Petch as biocontrol agent to termite Macrotermes gilvus Hagen has been tested in the laboratory.The purpose of this research is to study the symptomatology and lethal time of the termite M. gilvus fungus after infection by M. brunneum. The density of conidia at 1.21xlO6/mL showed as effective concentration in causing M. gilvus mortality, when compared to 1.08><106conidia/mL, and control. The infection stage of M. brunneum on the host until the death of its host occurred on day 2,and the sporulation of M. brunneum on the surface of the host integument occur on day 4. The entire surface of M. gilvus was covered by the mycelium and conidia of M. brunneum on day 7. Lethal time 50% of termite population of M. gilvus (LT50) was achieved in 5 days(5.14), and LT95 achieved on day 10 (10.03).